Neurosteroids and the Nervous System - King, Steven R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
While steroids from the periphery have profound effects on the nervous system, the nervous system also produces its own steroids de novo ((3z(Bneurosteroids(3y(B). The physiological importance of neurosteroids is beginning to be understood. These steroids potentially have roles in sedative/hypnotic behavior, anxiety, learning, and memory. At the cellular level, neurosteroids affect neuronal excitability, synaptic plasticity and cell proliferation and survival. Early findings hold promise for future strategies to treat specific psychologicalconditions and neurological diseases. This Brief will focus on the current state of understanding of brainderived neurosteroids.s
Keywords: Medicine; Neurosciences; Neurochemistry; Biomedicine; Neurosciences; Neurochemistry